Flow rule‐based routing protocol management system in software‐defined IoT sensor network for IoT applications. (21st April 2022) - Kumar, Karunanithi Praveen; Sivanesan, Perumal
Summary: In this article, a software‐defined (SDN)‐based Internet of things (IoT) sensor network (S‐ISN) architecture is proposed to fulfill the IoT applications in real time. The proposed system's architecture contains three planes, namely, data plane, control plane, and application plane, to enrich SDN in IoT applications. An IoT application‐based SDN controller is designed exclusively with two management rules—IoT application device management and IoT application‐based topology management. IoT application device management engages in controlling the functions of physical devices that lie on the data plane—path formation of the sensor (proactive, reactive, and hybrid) and reporting scheme management (query, time, and event) of the IoT sensor node. Likewise, IoT application topology management facilitates controlling network topology‐related issues using network structure management (data, location, group, and hierarchical) and next‐hop selection management (broadcast, location, and probabilistic) of the IoT sensor network. The above said management policies are achieved in real time to meet the applications of IoT. Hence, this S‐ISN scheme focuses on IoT application‐related issues with great flexibility in real time. Experimental results show that the network metrics have been improved by the proposed approach as compared with existing methods. Abstract : A software‐defined Internet of Things‐based sensor network (S‐ISN) architecture is proposed to fulfill the IoT applications in real time. The proposed system architecture contains three planes: data plane, control plane, and application plane to enrich software‐defined networking (SDN) in IoT applications. SDN controller is designed exclusively with two management rules, namely, IoT application device management and IoT application based topology management. The proposed approach improves certain performance metrics of the IoT sensor network.